Design of a transtelephonic ECG and thermometer device using the mobile phone - Yazıcı, Yüksel. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2005., 2005)
The need of effective and low cost personal and emergency monitoring telmedicine solutions are the main concerc of this porject. The patients who have heart diseases, ambulances are common example of possible emergency cases, while critical care telemetry and telemedicine personal follow-ups are important issues of telemonitoring. In order to support the above different growing application fields we created a combined store and forward (nearly real-time) facility that consists of a base unit and a telemedicine (mobile) unit using a commercial mobile phone and an external little capture card. Essentially this will allow the transmission of two vital biosignals (3 lead ECG, Body Temperature). This system can also be portable to other sensor applications. This design consist of a two part, the hardware whish is compose of three lead ECG and its peripheral circuits, power units and digital part which consists of PIC Microcontorller, TCP/IP chip and 512Kb EEPROM. Beside the ECG circuit a thermometer IC is used in 0.5 C resolution to measure body temprature. Transmission is performed through GPRS service network and the data is sent to certain IP address on internet using the commercial mobile phone. The software side which is provided by a PC assigned to Access server and Web Server. The data which are sent by patient remotely are stored in Access server and Web Page was designed to demonstrate and make it accessible from everywhere. This part of the project probably would be launched in patient observation center (hospital, specialized clinics etc).
Keywords: Telecommunication in medicine.; Electrocardiography.; Wireless communication systems.